2010
DOI: 10.1007/s13181-010-0013-x
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Venlafaxine and SSRIs in Deliberate Self-poisoning

Abstract: To compare the clinical features of deliberate selfpoisoning with venlafaxine and selective serotonin reuptake inhibitors (SSRIs) presenting to the emergency department of an Australian tertiary referral hospital. A retrospective cohort study comparing all 36 patients who presented with venlafaxine self-poisoning with 44 randomly selected patients with SSRI self-poisoning between 1997 and 2006. Patients who had overdosed on venlafaxine were older (mean age 37.4 versus 28.8 years, p≤0.001) and generally exhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 17 publications
1
17
0
2
Order By: Relevance
“…However, the incidence of serotonin toxicity between the groups was not statistically significant (P ¼ 0.066). 41 The genotype frequencies for the SSRIs versus the SNRIs is included in Table 2, and they are similar. Other non-genetic factors which also warrant further study include pharmacokinetic and pharmacodynamic parameters, such as age, sex, weight (body composition), disease states and coingested medications.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…However, the incidence of serotonin toxicity between the groups was not statistically significant (P ¼ 0.066). 41 The genotype frequencies for the SSRIs versus the SNRIs is included in Table 2, and they are similar. Other non-genetic factors which also warrant further study include pharmacokinetic and pharmacodynamic parameters, such as age, sex, weight (body composition), disease states and coingested medications.…”
Section: Discussionmentioning
confidence: 94%
“…When we compared the DDDs for the agents ingested, the patients with serotonin toxicity had a higher median DDD (27) compared with patients without toxicity (18). Chan et al 41 similarly showed that following intentional poisoning with either SSRIs or the SNRI venlafaxine, the median DDD was higher in the venlafaxine group compared with the SSRI group (35 compared with 19). However, the incidence of serotonin toxicity between the groups was not statistically significant (P ¼ 0.066).…”
Section: Discussionmentioning
confidence: 96%
“…When comparing poisonings by SNRIs and SSRIs, patients who overdosed with venlafaxine were older (37.4 13 vs. 28.8  10.1, P= 0.001), had higher degree of suicidal intent, and had ingested more pills (Chan, Gunja & Ryan, 2010). However, these observations were explained by studies that suggested that venlafaxine is prescribed to patients with higher risk of suicidal ideation.…”
Section: Serotonin and Norepinephrine Reuptake Inhibitor 41 Historymentioning
confidence: 99%
“…In cases of suicide by drug overdose, TCAs have the highest fatal toxicity, followed by serotonin and noradrenalin reuptake inhibitors (SNRIs), specific serotonergic antidepressants (NaSSA) and SSRIs (Chan, Gunja & Ryan, 2010;Hawton et al, 2010). Therefore, when prescribing antidepressants, the physician should take into consideration the risk of an overdose -especially for patients that have a high risk of suicide attempt -as well as the relative efficacy and acceptability of the drug, possible interactions with other medications and alcohol, and concurrent physical morbidity.…”
Section: Worldwide Characteristics Of Antidepressants Self-poisoningmentioning
confidence: 99%
“…Results A few literature case reports focusing on venlafaxine as a misusing drug were here identified. The molecule was here typically ingested or snorted at dosages up to 10-15 times higher than those clinically advised, obtaining MDMA/amphetamine-like stimulant and psy-INTRODUCTION Venlafaxine, the first marketed serotonin-norepinephrine reuptake inhibitor (Wyeth Laboratories, 2006), has now become one of the most frequently prescribed antidepressants worldwide, despite some concerns about its toxicity in overdose (Buckley and McManus, 2002;Whyte et al, 2003;Cheeta et al, 2004;Morgan et al, 2004;Cipriani et al, 2007;Rubino et al, 2007;Chan et al, 2010;Hawton et al, 2010;Launiainen et al, 2011). With a maximum recommended dosage of 375 mg, it is prescribed for a range of conditions, including major depression, generalized anxiety, social anxiety, and panic disorder (Bakish, 1999;Silverstone and Ravindran, 1999;Gorman et al, 2000;Thase et al, 2000;Thase et al, 2001;Anderson et al, 2008).…”
mentioning
confidence: 99%